Palladium Nanoparticles Doped on the Chitosan Nanofibers Modified with 2‐Aminobenzaldehyde as a Nanocatalyst in Cross‐Coupling Reactions. Issue 19 (15th May 2020) - Shahbazi, Esmaeil; Bahrami, Kiumars
Abstract: The palladium metal nanoparticles doped on the modified chitosan nanofibers with 2‐aminobenzaldehyde (CSNFs‐2‐AB−Pd (0)) were thoroughly characterized and applied as a novel heterogeneous catalyst in Heck and Suzuki C−C coupling reactions. This catalyst is exceptionally simple to handle and ecologically safe and temperate. The catalyst was essentially reused from the reaction mixture and reused sequential five times with low leakage. CSNFs‐2‐AB−Pd (0) was characterized using scanning electron microscopy, transmission electron microscopy, X‐ray diffraction, energy‐dispersive X‐ray spectroscopy and Fourier transform infrared. Abstract : The palladium metal nanoparticles‐doped on the modified chitosan nanofibers with 2‐aminobenzaldehyde (CSNFs‐2‐AB−Pd (0)) were thoroughly characterized and applied as a novel heterogeneous catalyst in Heck and Suzuki C−C coupling reactions. This catalyst is exceptionally simple to handle and ecologically safe and temperate. The catalyst was essentially reused from the reaction mixture and reused sequential five times with low leakage. CSNFs‐2‐AB−Pd (0) was characterized using scanning electron microscopy, transmission electron microscopy, X‐ray diffraction, energy‐dispersive X‐ray spectroscopy and FT‐IR.